Peningkatan Kemampuan Berbicara Melalui Media Film Dokumenter Pada Siswa Kelas VIII.2 SMP Negeri 2 Sungguminasa Kabupaten Gowa - Nurul Annisa Anwar; Abd. Munir; Indramini Indramini (Universitas Katolik Widya Karya Malang, 2023)
This study aims to improve the speaking skills of grade VIII.2 students of SMP Negeri 2 Sungguminasa through the media of documentary films for the 2022-2023 school year totaling 33 students. Data collection is carried out by test techniques. The data obtained were analyzed using descriptive methods by clarifying very high scores, high scores, medium scores and low scores. This type of research is classroom action research which consists of II cycles, namely cycle I with II meetings and cycle II with II meetings. This study focused on one class, namely class VIII.2 with a total of 33 students. The average score of learning outcomes in cycle I is 70.9 and learning outcomes from cycle II is 81.69. In the first cycle, the category of students who completed was 7 students with an achievement of 2.24%, the category of incomplete students was 25 students with a percentage of 78.1%. In cycle II the category of students who completed 28 with a percentage of 84.8% incomplete category 5 students with a percentage of 15%, which means that there was an increase in students' speaking skills from cycle I to cycle II of 81.41%. Based on the results of the research above, it can be concluded that the results of the speaking ability of grade VIII.2 SMP Negeri 2 Sungguminasa increased by using documentary film media, an increase of 81.41%.